Persistent Interactions of Core Histone Tails with Nucleosomal DNA following Acetylation and Transcription Factor Binding - Mutskov, Vesco (American Society for Microbiology, 1998)
In this study, we examined the effect of acetylation of the NH(2) tails of core histones on their binding to nucleosomal DNA in the absence or presence of bound transcription factors. To do this, we used a novel UV laser-induced protein-DNA cross-linking technique, combined with immunochemical and molecular biology approaches. Nucleosomes containing one or five GAL4 binding sites were reconstituted with hypoacetylated or hyperacetylated core histones. Within these reconstituted particles, UV laser-induced histone-DNA cross-linking was found to occur only via the nonstructured histone tails and thus presented a unique tool for studying histone tail interactions with nucleosomal DNA. Importantly, these studies demonstrated that the NH(2) tails were not released from nucleosomal DNA upon histone acetylation, although some weakening of their interactions was observed at elevated ionic strengths. Moreover, the binding of up to five GAL4-AH dimers to nucleosomes occupying the central 90 bp occurred without displacement of the histone NH(2) tails from DNA. GAL4-AH binding perturbed the interaction of each histone tail with nucleosomal DNA to different degrees. However, in all cases, greater than 50% of the interactions between the histone tails and DNA was retained upon GAL4-AH binding, even if the tails were highly acetylated. These data illustrate an interaction of acetylated or nonacetylated histone tails with DNA that persists in the presence of simultaneously bound transcription factors.